Hydrocracking catalyst for preparing aviation fuel as well as preparation method and application of hydrocracking catalyst
The hydrocracking catalyst combined with mesoporous zirconia sulfide and Ni-laden carrier solves the problem that existing catalyst products are difficult to meet the requirements of the number of carbon atoms of aviation fuel, and achieves efficient catalysis under mild conditions to meet the needs of aviation fuel.
Patent Information
- Application Number
- CN202510161977.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-02-14
AI Technical Summary
The products of existing polyolefin hydrocracking catalysts are difficult to meet the carbon atom number requirements of aviation fuels, and they need to rely on precious metal elements to achieve higher catalytic activity.
Mesoporous zirconia sulfide (catalyst I) is used to combine with Ni-supported support (catalyst II) to form a non-precious metal hydrocracking catalyst. Through specific preparation methods and proportional settings, the efficiency and selectivity of the catalyst are achieved.
Without the use of precious metal elements, the polyolefin hydrocracking reaction is efficiently carried out under mild conditions. The C8~C15 hydrocarbons in the product are highly selective, which meets the carbon atom number requirements of aviation fuel and achieves a high aviation fuel yield.
Smart Images

Figure CN119633850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a hydrocracking catalyst for preparing aviation fuel, a preparation method and an application thereof. Background Art
[0002] Polyolefins (such as polyethylene, polypropylene, etc.) are used everywhere in our lives. However, due to their acid and alkali resistance and good stability, polyolefin plastics are difficult to degrade in the natural environment, causing serious pollution to the environment. Traditional methods of treating polyolefin waste plastics, such as incineration, pyrolysis, biodegradation and landfill, all have their own shortcomings. For example, incineration wastes energy, landfill pollutes the soil, pyrolysis consumes a lot of energy, and biodegradation is difficult to achieve large-scale industrial production.
[0003] Hydrocracking usually has mild reaction conditions and a narrow carbon number distribution of the product, and is an efficient means of polyolefin recovery. However, traditional polyolefin hydrocracking relies on precious metal catalysts such as Pt and Ru, which are expensive and easily poisoned, making them difficult to prepare on a large scale, and their industrial applications are limited. In addition, the current aviation fuel (C8~C 15 ) is mainly prepared from petroleum products through complex processes. Not only is the process cumbersome and economically costly, but it also increases the degree of dependence on petroleum raw materials. The carbon number of the product of polyolefin hydrocracking is affected by the catalyst, so the hydrocracking catalysts used for different products cannot be used interchangeably. The products of existing hydrocracking catalysts are difficult to meet the carbon number requirements of aviation fuel. Therefore, it is particularly important to develop a non-precious metal catalyst that can efficiently catalyze the hydrocracking of polyolefins to produce aviation fuel under mild conditions. Summary of the invention
[0004] In order to solve the above technical problem, that is, the existing polyolefin hydrocracking catalysts have products that are difficult to meet the carbon number requirements of aviation fuel and need to rely on precious metal elements to achieve high catalytic activity, the present invention provides a hydrocracking catalyst for producing aviation fuel and its preparation method and application. The catalyst of the present invention can enable the polyolefin hydrocracking reaction to be carried out under mild conditions without using precious metal elements, and has a high C8~C 15 Hydrocarbon selectivity.
[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a hydrocracking catalyst for producing aviation fuel, comprising a catalyst I and a catalyst II; the catalyst I is mesoporous sulfided zirconium oxide; the catalyst II comprises a carrier and a Ni element loaded on the carrier; the catalyst I is formed by solid-phase calcination of a mixture of (NH4)2SO4 and ZrOCl2·8H2O.
[0006] In the present invention, the above-mentioned catalyst I and catalyst II are compounded to achieve a higher catalytic activity without using precious metal elements, so that the polyolefin hydrocracking reaction can be carried out under mild conditions. In addition, the catalyst of the present invention can reduce the C8~C 15 The proportion of hydrocarbons (hydrocarbons with carbon atoms of 8 to 15) is relatively high, which can meet the carbon atom number requirements of aviation fuel and achieve a higher aviation fuel yield.
[0007] The hydrocracking catalyst of the present invention is composed of a composite of catalyst I and catalyst II, so that there is a certain spatial distance between the Ni active site and catalyst I, which can make the polyolefin hydrocracking process proceed according to a suitable reaction route, avoid deep cracking of the product, and improve the C8~C 15 If the active component (Ni element) in catalyst II is loaded into catalyst I, the spatial distance between the active site in catalyst I and Ni will be too close, and the content of low-carbon hydrocarbons in the product will be large, C8~C 15 The hydrocarbon content is too low.
[0008] In addition, the formation mode of catalyst I also affects the C8~C 15 The catalyst I in the present invention is formed by solid-phase calcination of a mixture of (NH4)2SO4 and ZrOCl2·8H2O, which can make the catalyst I have a suitable pore structure, can accommodate and stabilize reaction intermediates and products of larger sizes, is beneficial to the formation of high carbon number products, and can make the C8~C 15 Hydrocarbons have a higher proportion. When the catalyst I is formed by impregnation and roasting, the C8~C 15 The selectivity to hydrocarbons is low.
[0009] Preferably, the mass ratio of the catalyst I to the catalyst II is 0.25-1:1.
[0010] In the hydrocracking catalyst of the present invention, when the proportion of catalyst I is too large, deep cracking will occur, resulting in C8~C 15 The selectivity of hydrocarbons decreases, and excessive small molecular hydrocarbons are generated; when the proportion of catalyst II is too large, the acid sites are insufficient, which will cause the activity of catalyzing polyolefin hydrocracking to decrease, and more high-carbon waxy substances will be generated. The mass ratio of catalyst I to catalyst II is set to 0.25~1:1, which can further improve the C8~C 15 Selectivity of hydrocarbons.
[0011] Preferably, the molar ratio of ZrOCl2·8H2O to (NH4)2SO4 is 1:4-10.
[0012] By increasing the amount of (NH4)2SO4 relative to ZrOCl2·8H2O, the strong acid sites in Catalyst I can be increased, thereby improving the catalyst activity.
[0013] Preferably, in the catalyst I, the content of single Ni is 2-30 wt%.
[0014] Preferably, the carrier is an inert carrier.
[0015] Furthermore, the inert carrier is SiO2 and / or Al2O3.
[0016] In a second aspect, the present invention provides a method for preparing the hydrocracking catalyst, comprising the following steps: S1: (NH4)2SO4 and ZrOCl2·8H2O were mixed and ground, and then calcined in an oxygen atmosphere to obtain catalyst I; S2: mixing the nickel source solution and the carrier, and performing reduction calcination to obtain catalyst II; S3: Mixing catalyst I and catalyst II to obtain a hydrocracking catalyst.
[0017] Preferably, in step S1, the aerobic atmosphere is an air atmosphere; the calcination temperature is 600-620° C., and the calcination time is 4.5-5.5 h.
[0018] Preferably, in step S2, the reduction roasting process is carried out in a hydrogen atmosphere at a temperature of 600-650° C. for 3-5 h.
[0019] In a third aspect, the present invention provides the use of the hydrocracking catalyst in catalyzing the hydrocracking of polyolefins to produce aviation fuel, wherein the aviation fuel is a hydrocarbon having 8 to 15 carbon atoms.
[0020] Preferably, the application comprises the following steps: after mixing and grinding the polyolefin powder and the hydrocracking catalyst, introducing hydrogen to carry out a hydrocracking reaction.
[0021] Preferably, in the process of catalytic polyolefin hydrocracking to produce aviation fuel, the hydrogen pressure is 0.2-1 MPa and the reaction temperature is 200-350 °C.
[0022] Preferably, the polyolefin is one or more of polyethylene, polypropylene and polystyrene, with a weight average molecular weight (M w ) is 150000~260000 Da.
[0023] Preferably, the process of catalytic polyolefin hydrocracking to produce aviation fuel is carried out in a fixed bed, a fluidized bed or an autoclave.
[0024] Compared with the prior art, the present invention has the following advantages: (1) In the hydrocracking catalyst of the present invention, by using a specific catalyst I and a catalyst II compound, and by using (NH4)2SO4 and ZrOCl2·8H2O mixed solid phase calcination to form catalyst I, it is possible to achieve a higher catalytic activity without using precious metal elements, so that the polyolefin hydrocracking reaction can be carried out under mild conditions, and has a higher C8~C 15 Hydrocarbon selectivity, the product can meet the carbon atom number requirements of aviation fuel and achieve a higher aviation fuel yield.
[0025] (2) In the hydrocracking catalyst of the present invention, by setting the mass ratio between catalyst I and catalyst II to 0.25-1:1, the C8-C 15 Hydrocarbon selectivity, so that the polyolefin hydrocracking products have a higher content of C8~C 15 Hydrocarbons. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the distribution diagram of the liquid product obtained after the hydrocracking of polyolefin in Example 1.
[0027] Figure 2 is the XRD pattern of catalyst I prepared in Example 1.
[0028] Figure 3 This is a nitrogen absorption and desorption diagram of catalyst I prepared in Example 1.
[0029] Figure 4 This is a scanning electron microscope image of catalyst I prepared in Example 2.
[0030] Figure 5 This is the XRD pattern of Catalyst II prepared in Example 2.
[0031] Figure 6 This is the nitrogen adsorption diagram of catalyst I prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with the embodiments.
[0033] First, the present invention relates to a hydrocracking catalyst for preparing aviation fuel, comprising a catalyst I and a catalyst II; the catalyst I is mesoporous sulfided zirconium oxide; the catalyst II comprises a carrier and a Ni element loaded on the carrier; the catalyst I is formed by solid-phase calcination of a mixture of (NH4)2SO4 and ZrOCl2·8H2O.
[0034] In some specific embodiments, the mass ratio of the catalyst I to the catalyst II is 0.25-1:1.
[0035] In some specific embodiments, the molar ratio of ZrOCl2·8H2O to (NH4)2SO4 is 1:4-10.
[0036] In some specific embodiments, in the catalyst I, the content of Ni single substance is 2-30 wt%.
[0037] In some specific embodiments, the carrier is an inert carrier. The inert carrier can be selected from SiO2, Al2O3 or other inert carriers commonly used in industry, and the specific type is not limited in the present invention.
[0038] Second, the present invention relates to a method for preparing the hydrocracking catalyst, comprising the following steps: S1: (NH4)2SO4 and ZrOCl2·8H2O were mixed and ground, and then calcined in an oxygen atmosphere to obtain catalyst I; S2: mixing the nickel source solution and the carrier, and performing reduction calcination to obtain catalyst II; S3: Mixing catalyst I and catalyst II to obtain a hydrocracking catalyst.
[0039] In some specific embodiments, in step S1, the oxygen atmosphere is an air atmosphere; the calcination temperature is 600-620° C., and the calcination time is 4.5-5.5 h.
[0040] In some specific embodiments, in step S2, the reduction calcination process is carried out in a hydrogen atmosphere at a temperature of 600-650° C. for 3-5 h.
[0041] Thirdly, the present invention relates to the use of the hydrocracking catalyst in catalyzing the hydrocracking of polyolefins to produce aviation fuel, wherein the aviation fuel is a hydrocarbon having 8 to 15 carbon atoms.
[0042] In some specific embodiments, the application includes the following steps: mixing and grinding the polyolefin powder and the hydrocracking catalyst, and then introducing hydrogen to carry out a hydrocracking reaction.
[0043] In some specific embodiments, during the process of catalytic polyolefin hydrocracking to produce aviation fuel, the hydrogen pressure is 0.2-1 Mpa and the reaction temperature is 200-350 °C.
[0044] In some specific embodiments, the polyolefin is one or more of polyethylene, polypropylene and polystyrene, and the weight average molecular weight (M w ) is 150000~260000 Da.
[0045] In some specific embodiments, the process of catalytic polyolefin hydrocracking to produce aviation fuel is carried out in a fixed bed, a fluidized bed or an autoclave.
[0046] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0047] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0048] Example 1 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1. The mixture was allowed to stand at room temperature for 18 h and calcined at 600 °C in air for 5 h to obtain catalyst I (S / Zr=6). Figure 2 As shown, the nitrogen adsorption and desorption data are as follows Figure 3 shown.
[0049] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 2 wt% (i.e., the Ni content in catalyst II was 2 wt%).
[0050] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.2 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons is 74.8%, and the liquid product distribution diagram is as follows Figure 1 shown.
[0051] Example 2 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 4:1. The mixture was allowed to stand at room temperature for 18 h and calcined at 600 °C in air for 5 h to obtain catalyst I (S / Zr=4). The SEM image of the mixture is shown in Figure 2. Figure 4 As shown ( Figure 4 The scale bar in the lower right corner means that the sum of all the small grids is 5.00 μm).
[0052] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by equal volume impregnation method (the volume of nickel nitrate aqueous solution was equal to the pore volume of nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 15 wt% (i.e., the Ni content in catalyst II was 15 wt%). The XRD pattern of catalyst II is shown in Figure 2. Figure 5 As shown, it is shown that the Ni element exists in the form of Ni metal element.
[0053] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 1 MPa hydrogen, reacted at 200 °C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 60.4%.
[0054] Example 3 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 10:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in an air atmosphere for 5 h to obtain catalyst I (S / Zr=10).
[0055] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 30 wt% (i.e., the Ni content in catalyst II was 30 wt%).
[0056] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 25 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.5 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 72.7%.
[0057] Example 4 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0058] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 30 wt% (i.e., the Ni content in catalyst II was 30 wt%).
[0059] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of polypropylene powder (M w = 200000 Da, mixed and ground evenly, loaded into a fluidized bed reactor, introduced 1 MPa hydrogen, reacted at 300 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 80.5%.
[0060] Example 5 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 4:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in an air atmosphere for 5 h to obtain catalyst I (S / Zr=4).
[0061] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 10 wt% (i.e., the Ni content in catalyst II was 10 wt%).
[0062] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 100 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of the polyolefin mixture powder (composed of M w = 260000 Da polystyrene 0.5 g and M w =150000 Da polyethylene 0.5 g), mixed and ground evenly, loaded into a fixed bed reactor, introduced 1 MPa hydrogen, reacted at 350 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 77.2%.
[0063] Example 6 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0064] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 10 wt% (i.e., the Ni content in catalyst II was 10 wt%).
[0065] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 500 mg of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into a fixed bed reactor, introduced 0.5 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 60.1%.
[0066] Example 7 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0067] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-alumina were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-alumina), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 10 wt% (i.e., the Ni content in catalyst II was 10 wt%).
[0068] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 500 mg of polyethylene powder (M w =150000 Da, mixed and ground evenly, loaded into a fixed bed reactor, introduced 0.2 MPa hydrogen, reacted at 250 °C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 75.7%.
[0069] Example 8 In this embodiment, a hydrocracking catalyst is prepared according to the following steps, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0070] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 2 wt% (i.e., the Ni content in catalyst II was 2 wt%).
[0071] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 30 mg of the catalyst I prepared in step S1, 120 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.2 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 68.9%.
[0072] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, the catalyst I is prepared by an impregnation and calcination method; the remaining steps are the same as those of Example 1. Specifically, the hydrocracking catalyst is prepared according to the following steps in this comparative example, and is used to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I The ammonium sulfate aqueous solution and Zr(OH)4 were mixed by equal volume impregnation method (the volume of ammonium sulfate aqueous solution was equal to the pore volume of Zr(OH)4), ultrasonicated for 2 h to form a uniform mixture, and calcined at 600 °C for 5 h in air atmosphere to obtain catalyst I (S / Zr=6). Its nitrogen adsorption and desorption data are shown in Figure 6 shown.
[0073] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 2 wt% (i.e., the Ni content in catalyst II was 2 wt%).
[0074] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the catalyst I prepared in step S1, 100 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.2 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 45.8%.
[0075] Comparing Example 1 with Comparative Example 1, it can be seen that compared with the impregnation calcination method, the mixed solid phase calcination method of the present invention is used to prepare the catalyst I, which can improve the C8~C 15 The reason for this is that the preparation method affects the pore structure of catalyst I (by Figure 3 and Figure 6 It can be seen that when the mixed solid phase calcination method is used, the prepared catalyst I can have a suitable pore structure, which can accommodate and stabilize the reaction intermediates and products of larger sizes, and is beneficial to the formation of high carbon number products, thereby making the C8~C 15 Hydrocarbons have a higher proportion.
[0076] Comparative Example 2 The difference between this comparative example and Example 1 is that this comparative example does not adopt the form of compounding catalyst I and catalyst II, but loads the active component (Ni) in catalyst II into catalyst I; the rest of the steps are the same as those in Example 1. Specifically, this comparative example prepares a hydrocracking catalyst according to the following steps, and uses it to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0077] S2: Load Ni The nickel nitrate aqueous solution and catalyst I were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of catalyst I), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered hydrocracking catalyst in which the Ni loading was 2 wt% (i.e., the Ni content in catalyst II was 2 wt%).
[0078] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 50 mg of the hydrocracking catalyst prepared in step S2 and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.2 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 50.1%.
[0079] Comparing Example 1 with Comparative Example 2, it can be seen that compared with loading the active component (Ni) in Catalyst II into Catalyst I, the present invention adopts a compounding method of Catalyst I and Catalyst II to improve the C8~C 15 Selectivity for hydrocarbons. The reason for this is that the compounding of catalysts I and II enables a larger spatial distance between the Ni active site and catalyst I, so that the polyolefin hydrocracking process proceeds according to a suitable reaction route and avoids deep cracking of the product; whereas if Ni is loaded in catalyst I, the spatial distance between the active site in catalyst I and Ni will be too close, resulting in a higher content of low-carbon alkanes in the product.
[0080] Comparative Example 3 The difference between this comparative example and Example 5 is that the mass ratio between catalyst I and catalyst II is changed from 1:1 to 1.5:1 in this comparative example; the remaining steps are the same as those in Example 5. Specifically, this comparative example prepares a hydrocracking catalyst according to the following steps, and uses it to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 4:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in an air atmosphere for 5 h to obtain catalyst I (S / Zr=4).
[0081] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 10 wt% (i.e., the Ni content in catalyst II was 10 wt%).
[0082] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 120 mg of the catalyst I prepared in step S1, 80 mg of the catalyst II prepared in step S2, and 1 g of the polyolefin mixture powder (composed of M w = 260000 Da polystyrene 0.5 g and M w =150000 Da polyethylene 0.5 g), mixed and ground evenly, loaded into a fixed bed reactor, introduced 1 MPa hydrogen, reacted at 350 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 53.8%.
[0083] Comparing Example 5 with Comparative Example 3, it can be seen that in the hydrocracking catalyst composed of Catalyst I and Catalyst II, when the proportion of Catalyst I is too large, it will cause the C8~C 15 The decrease in hydrocarbon selectivity may be due to the deep cracking of polyolefins, which produces excessive small molecular hydrocarbons.
[0084] Comparative Example 4 The difference between this comparative example and Example 8 is that the mass ratio of catalyst I to catalyst II is changed from 0.25:1 to 0.15:1 in this comparative example; the remaining steps are the same as those in Example 8. Specifically, this comparative example prepares a hydrocracking catalyst according to the following steps, and uses it to catalyze the hydrocracking of polyolefins to produce aviation fuel: S1: Preparation of Catalyst I Ammonium sulfate and zirconium oxychloride octahydrate were ground at room temperature to obtain a uniform solid mixture with a molar ratio of (NH4)2SO4 to ZrOCl2·8H2O of 6:1, which was allowed to stand at room temperature for 18 h and calcined at 600 °C in air atmosphere for 5 h to obtain catalyst I (S / Zr=6).
[0085] S2: Preparation of Catalyst II The nickel nitrate aqueous solution and nano-silica were mixed by an equal volume impregnation method (the volume of the nickel nitrate aqueous solution was equal to the pore volume of the nano-silica), ultrasonicated for 2 h to form a uniform mixture, and then calcined at 600 °C for 3 h in a hydrogen atmosphere to obtain a powdered catalyst II, in which the Ni loading was 2 wt% (i.e., the Ni content in catalyst II was 2 wt%).
[0086] S3: Catalytic hydrocracking of polyolefins to produce aviation fuel Weigh 20 mg of the catalyst I prepared in step S1, 130 mg of the catalyst II prepared in step S2, and 1 g of polyethylene powder (M w = 150000 Da, mixed and ground evenly, loaded into an autoclave reactor, introduced 0.2 MPa hydrogen, reacted at 250 ° C until the polyolefin conversion rate was 100%, and the aviation fuel (C8~C 15 The yield of hydrocarbons was 25.7%.
[0087] Comparing Example 8 with Comparative Example 4, it can be seen that in the hydrocracking catalyst composed of Catalyst I and Catalyst II, when the proportion of Catalyst II is too large, it will cause the C8~C 15 The selectivity of hydrocarbons decreases, which may be due to insufficient acid sites, resulting in a decrease in the activity of catalytic polyolefin hydrocracking and the generation of more high-carbon waxy substances.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A hydrocracking catalyst for preparing aviation fuel, characterized in that: The catalyst comprises a catalyst I and a catalyst II; the catalyst I is mesoporous sulfided zirconium oxide; the catalyst II comprises a carrier and a Ni element loaded on the carrier; the catalyst I is formed by solid-phase calcination of a mixture of (NH4)2SO4 and ZrOCl2·8H2O.
2. The hydrocracking catalyst according to claim 1, characterized in that The mass ratio of the catalyst I to the catalyst II is 0.25-1:
1.
3. The hydrocracking catalyst according to claim 1, characterized in that The molar ratio of ZrOCl2·8H2O to (NH4)2SO4 is 1:4-10.
4. The hydrocracking catalyst according to claim 1, characterized in that In the catalyst II, the content of Ni single substance is 2-30 wt%.
5. The hydrocracking catalyst according to claim 1, characterized in that The carrier is an inert carrier.
6. A method for preparing the hydrocracking catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: (NH4)2SO4 and ZrOCl2·8H2O were mixed and ground, and then calcined in an oxygen atmosphere to obtain catalyst I; S2: mixing the nickel source solution and the carrier, and performing reduction calcination to obtain catalyst II; S3: Mixing catalyst I and catalyst II to obtain a hydrocracking catalyst.
7. The preparation method according to claim 6, characterized in that: In step S1, the oxygen atmosphere is an air atmosphere; the calcination temperature is 600-620° C., and the calcination time is 4.5-5.5 h.
8. The preparation method according to claim 6, characterized in that: In step S2, the reduction calcination process is carried out in a hydrogen atmosphere at a temperature of 600-650° C. for 3-5 h.
9. Use of the hydrocracking catalyst according to any one of claims 1 to 5 in catalyzing the hydrocracking of polyolefins to produce aviation fuel, characterized in that: The aviation fuel is a hydrocarbon with 8 to 15 carbon atoms.
10. The use according to claim 9, characterized in that: In the process of catalytic polyolefin hydrocracking to produce aviation fuel, the hydrogen pressure is 0.2-1 Mpa and the reaction temperature is 200-350°C.
Citation Information
Patent Citations
Preparation method of C12 olefin
CN111995491A
Difunctional coupling catalyst for hydrocracking of waste plastics and preparation method of difunctional coupling catalyst
CN114471597A
Catalyst for preparing olefin through CO2 hydrogenation as well as preparation method and application of catalyst
CN118976513A
Application of zirconium sulfate oxide solid superacid and nickel carbon catalyst in concerted catalysis of lignite model compound for hydrodeoxygenation
CN119215937A
Supported solid superacid catalysts and method for making them
WO1997018892A1